Distal bile duct cancer: radical (R0 > 1 mm) resection achieves favorable survival - Tjaden, Christin; Hinz, Ulf; Klaiber, Ulla; Heger, Ulrike; Springfeld, Christoph; Goeppert, Benjamin; Schmidt, Thomas; Mehrabi, Arianeb; Strobel, Oliver; Berchtold, Christoph; Schneider, Martin; Diener, Markus K.; et al. (Annals of surgery, 2023)
Objective: - Evaluation of the outcome after resection for distal bile duct cancer (DBC) with focus on the impact of microscopic histopathological resection status R0 (>1 mm) versus R1 (≤1 mm) vs R1 (direct). - Summary Background Data: - DBC is a rare disease for which oncologic resection offers the only chance of cure. - Methods: - Prospectively collected data of consecutive patients undergoing pancreaticoduodenectomy for DBC were analyzed. Histopathological resection status was classified according to the Leeds protocol for pancreatic ductal adeno carcinoma (PDAC) (PDAC; R0 >1 mm margin clearance vs R1 ≤1 mm vs R1 direct margin involvement). - Results: - A total of 196 patients underwent pancreaticoduodenectomy for DBC. Microscopic complete tumor clearance (R0>1 mm) was achieved in 113 patients (58%). Median overall survival (OS) of the entire cohort was 37 months (5- and 10-year OS rate: 40% and 31%, respectively). After R0 resection, median OS increased to 78 months with a 5-year OS rate of 52%. Negative prognostic factors were age >70 years (P < 0.0001, hazard ratio (HR) 2.48), intraoperative blood loss >1000 mL (P = 0.0009, HR 1.99), pN1 and pN2 status (P = 0.0052 and P = 0.0006, HR 2.14 and 2.62, respectively) and American Society of Anesthesiologists score >II (P = 0.0259, HR 1.61). - Conclusions: - This is the largest European single-center study of surgical treatment for DBC and the first to investigate the prognostic impact of the revised PDAC resection status definition in DBC. The results show that this definition is valid in DBC and that “true” R0 resection (>1 mm) is a key factor for excellent survival. In contrast to PDAC, there was no survival difference between R1 (≤1 mm) and R1 (direct).
Gesehen am 27.02.2023